Corruption and Nigerian political economy - Mikail, Ibrahim Kawuley (UUM Press, 2016)
The book analyses the background of corrupt practices in the annals of Nigerian political history from pre-colonial, colonial and post-colonial era down to the fourth democratic dispensation. The book also estab¬lishes a nexus between corruption and political economy in the Nigerian political theatre. Indeed, corrup¬tion undermines the rules of law, equity, transparency democratization and national development which breed poverty, insecurity and general underdevelopment among the populace.Meanwhile, the political economy approach and the theories of corruption and their application on Nigerian political economy is highlighted.The role of policy-makers and stakeholders with their policies and programmes on combat¬ing corruption is also analysed. Furthermore, the giant efforts of international organizations, civil society organizations (CSOs) and non-governmental organizations (NGOs) on combating the menace of corruption are also pointed out. The book serves as a guide to researchers on the subject matter and the freedom fighters with their anti-corruption crusade or mandates so as to proffer solutions to corrupt practices and scandals in Nigeria and beyond.